Feasibility of fetal echocardiography screening during first trimester in a low-risk population - Perumal, Ambika; Natarajan, Lalitha; Abraham, Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Prenatal identification of cardiac defect gives families the opportunity to receive counselling regarding the anticipated fetal and neonatal outcomes. Screening and diagnosis of congenital heart disease in the first trimester has increased over the past decade as almost all CHDs are already established by that time. Objective was to assess the feasibility of screening through first trimester echocardiography by a trained observer in low-risk populations. Methods: The study was conducted on a sample of 500 antenatal mothers of gestational age between 11-13 weeks+6 days attending a teaching hospital. Maternal age, weight, height, body mass index, parity, gestational age, obstetric history and past history were recorded. In addition to first trimester ultrasound screening for aneuploidy in foetuses, a simplified echocardiographic examination was performed. After obtaining the appropriate fetal position, Crown-rump length was documented. Nuchal translucency thickness was recorded. After examination with 2-dimensional sonography, the operator obtained the tricuspid flow and ductus venosus flow. Color flow mapping was applied for evaluating the 4-chamber view and three vessel tracheal views. Specific criteria developed for the 4-chamber view, 3 vessel trachea view, tricuspid flow and ductus venosus flow was used to assess feasibility. Results: Good feasibility was observed for all the views, with tricuspid flow showing 96% feasibility, Ductus Venosus showing 95% feasibility, 3VT view showing 90.1% feasibility and 4CV view having 89.7% feasibility. There was no significant association found between maternal BMI, CRL and the feasibility of fetal cardiac screening. Conclusions: Encouraging results of this study indicates the feasibility of fetal cardiac screening in low-risk population.